From Two‐ to Three‐Dimensional Structures of a Supertetrahedral Boran Using Density Functional Calculations. (12th April 2017) - Getmanskii, Iliya V.; Minyaev, Ruslan M.; Steglenko, Dmitrii V.; Koval, Vitaliy V.; Zaitsev, Stanislav A.; Minkin, Vladimir I.
Abstract: With help of the DFT calculations and imposing of periodic boundary conditions the geometrical and electronic structures were investigated of two‐ and three‐dimensional boron systems designed on the basis of graphane and diamond lattices in which carbons were replaced with boron tetrahedrons. The consequent studies of two‐ and three‐layer systems resulted in the construction of a three‐dimensional supertetrahedral borane crystal structure. The two‐dimensional supertetrahedral borane structures with less than seven layers are dynamically unstable. At the same time the three‐dimensional superborane systems were found to be dynamically stable. Lack of the forbidden electronic zone for the studied boron systems testifies that these structures can behave as good conductors. The low density of the supertetrahedral borane crystal structures (0.9 g cm −3 ) is close to that of water, which offers the perspective for their application as aerospace and cosmic materials.